Aversiveness of errors in performance monitoring and error related negativity in obsessive compulsive symptomatology - Nuñez Estupiñan, Xiomara (2021)
The error-related negativity is one of the most examined event-related potentials in the study of cognitive control, yet its functional significance has not been fully determined. The present dissertation had the objective to investigate the relationship between error processing and affective states manipulations in non-clinical samples and in OC symptomatology. Two studies constitute this dissertation. In study 1, we conducted a systematic review of studies investigating affective state manipulations, aversiveness of errors and the ERN. This review showed considerable evidence for ERN sensitivity to affect states experimental manipulations. In study 2, we aimed to explore the incidence of the error-related potentials at a gambling-type task (HiLo game) in a sample composed of people with high OCD symptomatology. Although the ERPs of interest were not elicited, we showed that the HiLo game is a promising paradigm to investigate the ERN in upcoming studies. In the general discussion, the results from the two studies are discussed in relation to the literature on error monitoring and affective conceptualizations.